The frequency of enthesopathies in the 14-15th century series of Bátmonostor-Pusztafalu - Józsa, László; Farkas, Gyula L.; Paja, László (Acta Biologica Szegediensis, 2004)
This study presents the frequency of enthesopathies in the osteological material of a medieval cemetery. The development of the phenomenon is explained as a result of the exerting way of living. The bony outgrows appear in the patellae and the calcanei the most frequently, and twice as much males are involved than females. The appearence of the lesions may be single, but in some cases multiple changes may also be seen on a skeleton.